Strategi Pengelolaan Sumber Daya Manusia di Madrasah Tsanawiyah ’Aisyiyah - Yohana Sazlila; Dien Nurmarina Malik Fadjar; Ahmad Subagyo; Muhamad Sofian Hadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Human Resource (HR) Management is the main foundation in supporting the success of educational institutions, including Madrasah Tsanawiyah (MTs) ’Aisyiyah. HR that is managed strategically can improve the quality of educational services and create a productive and spiritual learning environment. This study aims to analyze effective HR management strategies that are relevant to the context of madrasas, especially at MTs ’Aisyiyah. This research used a mixed method approach. namely a combination of quantitative and qualitative methods. Data were collected through observation, in-depth interviews, documentation, and distributing questionnaires to educators and school management. The results of the research indicate that there are four main strategies that are implemented effectively in HR management at MTs ’Aisyiyah: (1) Recruitment strategies based on Islamic values ​​and moral integrity, which ensure that prospective educators and education personnel have spiritual commitment and professional competence; (2) Implementation of continuous training and development designed to improve teacher capacity in teaching and character building; (3) Fair and transparent performance management, including a performance-based evaluation system and providing constructive feedback; and (4) Providing integrated spiritual motivation in school activities, such as regular religious studies and Islamic guidance. This study concludes that the integration of modern management principles and Islamic values ​​is able to create an effective and meaningful HR management system in the madrasa environment. Practical recommendations are also provided so that other Islamic educational institutions can adopt similar strategies in an effort to improve the quality of HR and educational services. These findings are expected to be a real contribution to the development of Islamic education management in Indonesia.